LC–MS/MS Method for Measurement of Thiopurine Nucleotides (TN) in Erythrocytes and Association of TN Concentrations With TPMT Enzyme Activity - Bajaj, Amol O.; Kushnir, Mark M.; Kish-Trier, Erik; Law, Rachel N.; Zuromski, Lauren M.; Molinelli, Alejandro R.; McMillin, Gwendolyn A.; Johnson-Davis, Kamisha L. (Frontiers in Pharmacology, 2022)
Monitoring concentrations of thiopurine metabolites (TM) is used clinically to prevent adverse effects in patients on thiopurine drug therapy. We developed LC-MS/MS method for the quantification of 6-thioguanine (6-TG) and 6-methylmercaptopurine (6-MMP) in red blood cells (RBCs). The method utilizes an automated RBCs separation from whole blood samples and washing of the separated RBCs. The lower limit of quantification of the method was 20 pmol/mL for 6-TG (~ 50 pmol/8x108 RBC) and 400 pmol/mL for 6-MMP (~1000 pmol/8x108 RBC). The total imprecision of the assay was <3.0%. Upper limit of linearity for 6-TG and 6-MMP was 750 pmol/mL and 15,000 pmol/mL, respectively. Stability of the TM under pre- and post-analytically relevant conditions was also evaluated. Good agreement was observed between this method and validated LC-MS/MS methods of three laboratories, except for ~40% low bias for 6-MMP observed in one of the methods. Assessment of the association between 6-TG and 6-MMP concentrations with thiopurine S-methyltransferase (TPMT) phenotype and genotype demonstrated difference in the observed TM concentrations between the TPMT groups with normal and intermediate activity which was approaching statistical significance in case of 6-TG (p=0.096) and was statistically significant in case of 6-MMP (p<0.0001). No statistically significant differences were observed in distribution of 6-TG and 6-MMP concentrations among samples of the groups with different genotype. It was also observed in our retrospective data analysis that the concentration of 6-TG and 6-MMP in pediatric samples were higher as compared to adults, but the difference was not statistically significant.